2021
DOI: 10.1007/s12027-021-00678-2
|View full text |Cite
|
Sign up to set email alerts
|

European Green Deal – the way to Circular Public Procurement

Abstract: The aim of this paper is to link the concept of green public procurement (GPP) to the nowadays popular circular economy (CE) concept by exploring the possibilities of circular public procurement. The legal framework will be specified at all stages of the suggested procurement cycle (preparation, tendering, execution, monitoring) and the connected instruments that support GPP will be summarized. In the research, ecolabelling and life-cycle costing will be highlighted as tools leading to Circular Public Procurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Moreover, circular procurement can also be understood as an approach that recognises the role that private and public authorities have in supporting the transition towards CE. Circular public procurement can significantly advance the adoption of circular business models by requiring green products and additional circularity goals in cooperation with suppliers (Tátrai and Diófási-Kovács, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, circular procurement can also be understood as an approach that recognises the role that private and public authorities have in supporting the transition towards CE. Circular public procurement can significantly advance the adoption of circular business models by requiring green products and additional circularity goals in cooperation with suppliers (Tátrai and Diófási-Kovács, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A systematic evaluation of the specialized literature was made to gather information regarding the issue [91]. The study's findings demonstrated that, despite the free market, the EGD prioritizes the environment and has an impact on entrepreneurial activity [92]. The EGD outlines the backdrop of governmental regulations and interventions that would distort entrepreneurial and competitive processes via fiscal tools, policies and other mechanism in order to accomplish the stated aims [93].…”
Section: Literaturementioning
confidence: 99%
“…27 Still, a mandatory EU exclusion would be more consistent with holding sustainability as a cardinal value in the scheme of EU procurement legislation. 28 Instead, exclusion is mandatory under EU law only in case of child labour (Art. 57(1)(f), which is also covered by just one of the many international instruments listed in Annex X (ILO Convention 182 on Worst Forms of Child Labour).…”
Section: What Sustainability Principle?mentioning
confidence: 99%